Antioxidant enzyme activities and lipid peroxidation products in heart tissue of subacute and subchronic formaldehyde-exposed rats: a preliminary study - Güleç, M; Songur, A; Sahin, S; Ozen, OA; Sarsilmaz, M; Akyol, O (Sage Publications Inc, 2006)
Objective: The aim of this experimental study was to evaluate the oxidant/antioxidant status and lipid peroxidation in the heart of rats exposed to formaldehyde (FA) inhalation for four weeks (subacute) or 13 weeks (subchronic) continuously. Methods and results: Sixty Wistar albino rats were divided into six groups randomly (ten in each group). The first and second groups were used as subacute and subchronic control groups. FA gas was generated from paraformaldehyde and pumped to a closed glass chamber. Rats were exposed to atmosphere containing 10 and 20 ppm FA (8 h/day, five days per week) during a four and 13 weeks period. After heart tissues were obtained and homogenized, thiobarbituric acid-reactant substances (TBARS) and nitric oxide (NO) levels, as well as superoxide dismutase (SOD) and catalase (CAT) activities, were measured. There were statistically significant findings in SOD and CAT activities in the study groups compared to the control group. Heart tissue SOD level was increased in the group exposed to subacute 10 and 20 ppm FA inhalation compared to the control group (P < 0.011 and < 0.0001). In addition, heart tissue SOD level was increased in the group exposed to subchronic 10 and 20 ppm FA inhalation compared to the corresponding control group (P < 0.001). On the other hand, there were statistically significant decreases in CAT activity in subacute 10 and 20 ppm groups compared to the corresponding control group (P < 0.012 and < 0.039, respectively). Although not significant, TBARS levels were increased in both subacute 10 ppm (P = 0.100) and subchronic 20 ppm (P = 0.053) groups compared to their corresponding control groups. Tissue NO levels were unchanged upon FA inhalation. In the correlation analyses, a meaningful relationship between SOD and CAT activities in subchronic 10 ppm group (r = -0.685, P < 0.029); SOD activity and TBARS level in subchronic 20 ppm group (r = -0.675, P < 0.032); and CAT activity and NO level in subchronic 20 ppm group (r = -0.810, P < 0.005) were found. Conclusion: From the findings of our study, it can be interpreted that subacute and subchronic FA inhalation may stimulate oxidative stress and thus, some secondary toxic effects in cardiac cells and tissue. This increase in the oxidative stress could not induce lipid peroxidation in the membranous structure of cardiac cells. An increased SOD enzyme activity was thought to be secondary to decreased CAT activity, as a compensation mechanism, preventing heart tissue from destruction induced by FA.
Keywords: catalase; formaldehyde; heart; nitric oxide; superoxide dismutase; thiobarbituric acid-reactant substances